Inhalation bioaccessibility estimation of polycyclic aromatic hydrocarbons from atmospheric particulate matter (PM10): Influence of PM10 composition and health risk assessment. (January 2021) - Sánchez-Piñero, Joel; Moreda-Piñeiro, Jorge; Concha-Graña, Estefanía; Fernández-Amado, María; Muniategui-Lorenzo, Soledad; López-Mahía, Purificación
Abstract: Polycyclic aromatic hydrocarbons (PAHs) inhalation bioaccessibility was assessed in 65 atmospheric particulate matter samples (PM10 ) collected at an Atlantic coastal European urban site. The proposed method consists on a physiologically based extraction (PBET) by using Gamble's solution followed by a vortex assisted liquid-liquid micro-extraction (VALLME) and quantification by high performance liquid chromatography with fluorescence detection (HPLC-FLD). The use of a micro-extraction technique combined with FLD detection, provides a simple, fast, sensitive, accurate and low-cost methodology to PAHs quantification in bioaccessible fractions. Accuracy of the bioaccessibility study was assessed by means of a mass balance approaches using a PM10 filter and a certified reference material (ERM-CZ100). High-moderate inhalation bioaccessibilities were found for phenanthrene (Phe), fluoranthene (Ft) and pyrene (Pyr) (average ratios in the 52–65% range); while dibenz (a, h)anthracene (DBahA), indeno (1, 2, 3-cd)pyrene (IP) and benzo (g, h, i)perylene (BghiP) were observed to be less bioaccessibles (average ratios in the 11–14% range). Relationship between PM10 composition (major ions, trace metals, equivalent black carbon (eBC) and UV-absorbing particulate matter (UVPM)) and PAHs bioaccessibility ratios was also assessed. Principal Component Analysis (PCA) showed that PAHs bioaccessibility percentage is dependent on anthropogenic (eBC, UVPM and Sb concentrations) and marine sources of PM10 . Predicted PAHs bioaccessibilities after applying a multiple linear regression model based on marine and anthropogenic source of PM10 could also be established. Health risk assessment of target PM10 -associated PAHs via inhalation was assessed considering bioaccessibility concentrations by using hazard index (HI) and BaP equivalent concentration (BaPeq ) approaches, suggesting no carcinogenic risk in the area during the sampling campaign. Graphical abstract: Image 1 Highlights: Inhalation bioaccessibility of PM10 -associated PAHs was estimated by Gamble's solution. PAHs bioaccessibilities decreased when the number of rings were increased. Correlation between PM10 properties and PAHs bioaccessibility percentages were observed. Inhalation health risk assessment posed by PM10 -associated PAHs was estimated using bioaccessible fraction.